Optimization Study of the Line Array Layout of Slope–Pendulum Wave Energy Conversion Device - Yue Zhao; Zhanhong Wan; Ze Li; Guiyu Cao (Journal of Marine Science and Engineering)
The development of wave energy is of great ecological and commercial value. This paper studies the linear vertical array arrangement of the slope–pendulum wave energy conversion device (S-PWEC). Based on the WEC-Sim open-source program, we build four wave energy-generating devices with linear vertical array distributions to study the power generation performance of the array platform and establish the factors influencing the array. S-PWEC is affected by radiation and a shading effect from neighboring devices in a linear vertical array configuration. The overall and individual power generation efficiencies are similar. An increase in the number of devices in the linear vertical array exacerbates the fluctuation of wave excitation moment and output power, indicating that there exists an optimal array configuration for maximizing the power generation efficiency. The performance of the array devices is significantly affected by the direction of incoming waves, and the spacing of the arrays should therefore be adjusted according to the periods of the sea state: increasing the spacing in small periods and decreasing the spacing in large periods can effectively improve the overall power generation. In the future, we will continue to study other array forms of S-PWEC to improve the conversion efficiency of array wave power generation devices.